Long Non-coding RNA BC168687 is Involved in TRPV1-mediated Diabetic Neuropathic Pain in Rats. (15th March 2018) - Liu, Chenglong; Li, Congcong; Deng, Zeyu; Du, Errong; Xu, Changshui
Highlights: Long non-coding RNA BC168687 is involved in diabetic neuropathic pain in rats. LncRNA BC168687 siRNA may reduce expression of TRPV1 receptors in DRG of DNP rats. ERK and p38 signaling pathways might be regulated by lncRNA BC168687 siRNA in diabetic neuropathic pain. Abstract: Long noncoding RNAs (lncRNAs) participate in a diverse range of molecular and biological processes, and dysregulation of lncRNAs has been observed in the pathogenesis of various human diseases. We observed alterations in mechanical withdrawal thresholds (MWT) and thermal withdrawal latencies (TWL) in streptozotocin (STZ)- induced diabetic rats treated with small interfering RNA (siRNA) of lncRNA BC168687. We detected expression of transient receptor potential vanilloid type 1 (TRPV1) in rat dorsal root ganglia (DRG) by a series of molecular experiments. We determined relative levels of tumor necrosis factor (TNF)- α and interleukin (IL)- 1β in rat serum by enzyme-linked immunosorbent assay (ELISA). In addition, we examined extracellular regulated protein kinases (ERK) and p38 mitogen- activated protein kinase (MAPK) signaling pathways by Western blot (WB). We showed that the MWT and TWL of diabetic rats increased significantly compared with control. Expression of TRPV1 receptors in DRG substantially decreased. Relative levels of TNF- α and IL- 1β in the serum of lncRNA BC168687 siRNA-treated rats were reduced. Phosphorylation (p)- ERK and p- p38 signaling pathways in DRG were also decreased. Taken together, we concluded lncRNA BC168687 siRNA may alleviate TRPV1- mediated diabetic neuropathic pain.